â€œReview of role of Uttarbasti in management of Vatashthila W.S.R. to Benign Prostate Hyperplasia.â€: Array - Indore, Sangram (Ayurline: International Journal of Research in Indian Medicine, 2020)
In Ayurved Samhitas, symptoms of benign prostate hyperplasia are described under vatashthila..The majority of men over the age of 50 years are considered to have urinary symptoms attributing to vatashthila (BPH). Although it is not as much life threatening, its clinical manifestations worsen the patientâ€™s quality of life. It is a senile disease and patient may not be fit for surgery due to cardio-respiratory problems .Uttarbasti has got definite contribution which encourages us to find solution for this burning problem of society. Uttarbasti is a prime approch for vatashthia so this topic was chosen for review.